Pickering Emulsion-Driven MXene/Silk Fibroin Hydrogels with Programmable Functional Networks for EMI Shielding and Solar Evaporation - Yin, Guang; Wu, Jing; Qi, Chengzhang; Zhou, Xinfeng; Yu, Zhong‑Zhen; Zhang, Hao‑Bin (Nano-Micro Letters, 2025)
Flexible and conformable nanomaterial-based functional hydrogels find promising applications in various fields. However, the controllable manipulation of functional electron/mass transport networks in hydrogels remains rather challenging to realize. We describe a general and versatile surfactant-free emulsion construction strategy to customize robust functional hydrogels with programmable hierarchical structures. Significantly, the amphipathy of silk fibroin (SF) and the reinforcement effect of MXene nanosheets produce sable Pickering emulsion without any surfactant. The followed microphase separation and self-cross-linking of the SF chains induced by the solvent exchange convert the composite emulsions into high-performance hydrogels with tunable microstructures and functionalities. As a proof-of-concept, the controllable regulation of the ordered conductive network and the water polarization effect confer the hydrogels with an intriguing electromagnetic interference shielding efficiency (~ 64 dB). Also, the microstructures of functional hydrogels are modulated to promote mass/heat transfer properties. The amino acids of SF and the surface terminations of MXene help reduce the enthalpy of water evaporation and the hierarchical structures of the hydrogels accelerate evaporation process, expecting far superior evaporation performance (~ 3.5 kg m⁻2 h⁻1) and salt tolerance capability compared to other hydrogel evaporators. Our findings open a wealth of opportunities for producing functional hydrogel devices with integrated structure-dependent properties. Highlights: 1 A versatile surfactant-free emulsion construction strategy is proposed to customize functional hydrogels. 2 The synergistic emulsification mechanism between amphiphilic polymers and MXene is comprehensively elucidated. 3 Programmable functional structures confer hydrogels with excellent EMI shielding and water evaporation performance.